The Role of Tea Tree Oil in Alleviating Palmitic Acid-Induced Lipid Accumulation in Bovine Hepatocytes - Yang, Tianyu; Ma, Xiaoyu; Jiang, Maocheng; Cheng, Zhiqiang; Datsomor, Osmond; Zhao, Guoqi; Zhan, Kang (Frontiers in Veterinary Science, 2022)
Tea tree oil (TTO) plays an important role in lipid metabolism, alleviating the inflammatory responses. Fatty liver is associated with lipid accumulation in hepatocytes, leading to inflammation. However, there is very limited information on the effects of TTO on lipid accumulation, and inflammation in bovine hepatocytes. This study aimed to evaluate whether TTO alleviates palmitic acid (PA)-induced lipid accumulation in bovine hepatocytes. Hepatocytes isolated from mid-lactating Holstein cows were pretreated with 100 μM PA for 72 h. Cells were either pretreated with PA alone (PA group) or with PA followed by 0.00625% TTO treatment for 12 h (PT group). Expression of fatty acid oxidant genes increased (P < 0.05) while fatty acid synthesis genes decreased (P < 0.05) in the PT group compared with the PA group. PA treatment resulted in increased (P < 0.05) expression of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), but these increases were less in the PT group (P < 0.05). Compared to the PA group, expression of phosphorylated (p)-p65 and p-inhibitor κBα (p-IκBα) was suppressed (P < 0.05) by TTO treatment. TTO treatment limited (P < 0.05) the increase in intracellular reactive oxygen species (ROS) and prevented (P < 0.05) a reduction in mitochondrial membrane potential observed in response to PA treatment. Expression of endoplasmic reticulum (ER) stress genes was reduced (P < 0.05) in the PT group compared with the PA group. Our results suggest that TTO treatment attenuates the effects of PA in hepatocytes, leading to fatty acid oxidation, decreased fatty acid synthesis, suppressed inflammatory response, and reduced ER stress. Taken together, the results of this study suggest that TTO treatment may be a promising therapeutic approach to imbalanced lipid homeostasis, inflammation and ER stress in dairy cows shortly before and after calving.